The Use of Dilemma Story to Enhance Speaking Skill at Third Semester of IAI As’adiyah Sengkang - Satriani; Inayah, Nur; Razaq, Yusuf; Widistari, Sri; Kafrawi, Muhammad (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The goal of this study is to see if using dilemma stories as a teaching tool can help students improve their speaking abilities. The third semester of IAI As'adiyah Sengkang was involved in this study, which employed a descriptive-quantitative method. Interviews were used to acquire data, which were subsequently documented and examined qualitatively. The adoption of the dilemma tale approach can increase students' speaking abilities in the third semester of IAI As'adiyah Sengkang, according to data analysis. The statistical analysis shows that the mean score of the student's accuracy in the pretest (2.45) is lower than in the post-test (3.3), that the mean score of the student's fluency in the pretest (2.4) is lower than in the post-test (3.45), and that the mean score of the student's comprehensibility in the pretest (2.9) is lower than in the post-test (3.3). (3.8). The table reveals that the significant difference between the pre-test and post-test results of the student's speaking ability is higher (10.76) than the inferential statistical analysis shows (1.729).